2019
DOI: 10.1007/s10585-019-10006-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with liver tumors treated with holmium-166 radioembolization

Abstract: Holmium-166 radioembolization is a palliative treatment option for patients with unresectable hepatic malignancies. Its influence on quality of life has not been evaluated yet. Since quality of life is very important in the final stages of disease, the aim of this study was to evaluate the effect of holmium-166 radioembolization on quality of life. Patients with hepatic malignancies were treated with holmium-166 radioembolization in the HEPAR I and II studies. The European Organization for Research and Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
1
7
0
3
Order By: Relevance
“…Treatment selection should be based on expected gain in survival AND adverse event profile. In our review on studies reporting quality of life after treatment with radioembolization, most included studies reported no significant change in quality of life (105). Our own study results are compliant with this finding:…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Treatment selection should be based on expected gain in survival AND adverse event profile. In our review on studies reporting quality of life after treatment with radioembolization, most included studies reported no significant change in quality of life (105). Our own study results are compliant with this finding:…”
Section: Discussionsupporting
confidence: 84%
“…although there was a decline in quality of life after one week, overall, quality of life was not significantly affected over time (105). Based on these findings in palliative patients, the impact of radioembolization on quality of life is limited.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…No other variables had a significant influence on the development of GHS. 17 The development of quality of life after treatment was confirmed in the HEPAR PLUS study, again showing a significant decrease in quality of life early after treatment (i.e., 3 weeks) with rapid recovery thereafter. 12 Apart from a temporary significant decrease in the role functioning scale, only nonsignificant temporary decreases were noticed after 166 Ho-microsphere radioembolization.…”
Section: Quality Of Lifementioning
confidence: 79%
“…The European Organization for Research and Treatment of Cancer QLQ-C30 and LMC21 questionnaires were used to evaluate quality of life in the HEPAR and HEPAR II studies. 17 Measurements were performed at baseline, 1 week, 6 weeks, and at 6, 9, and 12 months after treatment. The course of the global health status and symptom and functioning scales were analyzed using a linear mixed model.…”
Section: Quality Of Lifementioning
confidence: 99%